MPC-8 CLINICAL CHARACTERISTICS OF H3 K27-MUTATED GLIOMAS AT MIDLINE AND NEAR MIDLINE. (3rd December 2022) - Hayashi, Nobuhide; Fukai, Junya; Nakatogawa, Hirokazu; Kawaji, Hiroshi; Okita, Yoshiko; Kijima, Noriyuki; Shofuda, Tomoko; Yoshioka, Ema; Kanemastu, Daisuke; Katsuma, Asako; Sumida, Miho; Nakao, Naoyuki; et al.
Abstract: Background and Purpose: Diffuse midline glioma(DMG), H3K27 alterd (WHO 2021, CNS grade 4) is a type of tumor that mainly develops in the CNS's median. However, owing to its rarity, few comprehensive reports have been published. This report conducted a retrospective study on H3p.K27M mutation cases via the Kansai Molecular Diagnosis Network for CNS tumors. Materials and Methods: H3p.K27M mutation cases were analyzed out of 4128 total gene analysis specimens submitted for suspected glioma during the case accumulation period from May 2007 to July 2022. Results: There were 109 cases with the H3p.K27M mutation, of which 107 had the H3F3A mutation, and 2 had the HIST1H3B mutation. Of the 93cases that developed a tumor on or around the lateral ventricles of the brain along the midline of the CNS, affected sites included the thalamus (37 cases), brainstem (19 cases), spinal cord (11 cases), and other areas (15 cases), while 7 cases were of multifocal origin and 4 cases were unclassifiable. The patients' ages ranged from 4 to 76 years, with a mean and median age of 32.8 and 30 years, respectively (n = 88). The male to female ratio was 52:36. All cases had IDH-wild type with pMGMT methylation (9.6%), pTERT mutation (3.2%), TP53 mutation (56.5%), BRAF V600E mutation (1.1%), FGFR1 mutation (14.3%), or EGFR mutation (3.3%). Histopathological examination revealed the existence of WHO CNS grade 2, 3, and 4 tumors. Overall survival (OS) was confirmed in 38 cases, with a mean and median age of 15.0 and 11.9 months, respectively. The results of 51 cases in which prognosis was followed up on, suggested that the factors that contributed to the prolongation of OS were female sex (p = 0.0335), thalamus location (p = 0.0366), and irradiation of 50 Gy or more (p = 0.0237). Discussion/Conclusion: Based on a literature review, we report on the clinical characteristics of DMG in our cases, including the category of midline in DMG.